Rectovestibular fistula: Is treatment always required? - Raghunath, B V; Girish, M L; Jade, Rajashekhar (Indian Journal of Child Health, 2016)
The traditional teaching in the management of rectovestibular fistula involves corrective surgery, either in single or multiple stages. Usually, female children operated for the same are advised cesarean section during childbirth to prevent damage to the neoanus. Herein, we report a story of a 68-year-old woman with untreated rectovestibular fistula and has given birth to five children without any sequalae.